Integration of Traditional and Modern Materials for Visual Comfort in Bayan Village Weaving House - Gusti Ayu Putu Selina Dewi; Nimas Sekarlangit (Universitas Sebelas Maret Surakarta, 2025)
The Weaving Production Houses in Bayan Village serve as dedicated spaces for weaving activities. Three permanent buildings, Fetung Bayan, Jajaq Bayan, and Belida Bayan, are primary weaving production facilities. Visual comfort is critical in supporting weaving activities from morning until evening. Ensuring optimal lighting conditions is essential to maintaining productivity and minimising visual strain for weavers. This study aims to identify the most effective material combinations to enhance visual comfort within these weaving spaces. A descriptive-quantitative research approach is employed, utilising DIALux simulation software to develop strategies for optimising visual comfort. The findings suggest that combining traditional and modern materials improves lighting conditions. The recommended configuration includes galvalume ceilings with a 78% reflection factor, woven bamboo (bedeg) walls with a 40% reflection factor, and concrete flooring with an 80% reflection factor. Additionally, shading elements and a Window-to-Wall Ratio (WWR) of 40% are proposed to enhance daylight control and reduce glare, ensuring a well-balanced luminous environment for weaving activities.